Pariwisata Dalam Perspektif Actor Network Theory (Studi Kasus Top Selfie Pinusan Kragilan Desa Pogalan, Jawa Tengah, Indonesia) - Bagus Trianggono; Pamerdi Giri Wiloso; Gatot Sasongko (Universitas Merdeka Malang, 2018)
Top Selfie Pinusan Kragilan (TSPK) is a new tourist destination in Magelang Regency. This destination is developed and managed independently by the community. In the context of this research, researchers want to examine the networking process among stakeholders in developing TSPK. The researcher used Actor Network Theory (ANT) as an analytical framework. The purpose of this study is to describe the role of actors in tourism development in TSPK. This study used qualitative research methods. Data collection is done by observation, documentation, in-depth interviews, and Focus Group Discussion (FGD). For analysis of the network process the researcher divides in two phases, namely the pioneering phase and the phase of TSPK development. The results showed that there was a lot of dynamics in the pioneering process until its development. These dynamics occur in the elements involved in the network and the dynamics of the controller in the network. Then the translation and intermediary processes experience dynamics, in the process of pioneering it runs perfectly, but during the development period it cannot run perfectly due to conflict. Based on these findings the researchers suggested that the TSPK managers involve the Magelang District Tourism Office to develop TSPK in the future. Then the suggestion for further research is that the next researcher can conduct research related to innovation in developing TSPK and strengthening the capacity of pokdarwis in the development of TSPK in the future.